Pengaruh Quality of Friendship terhadap Hardiness Siswa Islamic Boarding School di Kota Padang - Jannah, Izzahthul; Nio, Suci Rahma (Lembaga Yasin AlSys, 2024)
Islamic Boarding School is a dormitory-based Islamic school that combines a regular curriculum and a religious curriculum. The personality characteristic of hardiness is needed so that students can navigate the systems, regulations and changes that exist in Islamic boarding schools. One of the variables that can influence hardiness is the quality of friendship. The aim of this research is to see the influence of quality of friendship on the hardiness of Islamic boarding school students at junior high level in Padang City. The method used in this research is a quantitative survey with a correlation method. The subjects in this research were junior high school students studying at an Islamic boarding school in Padang City which is under the auspices of the Ministry of Education and Culture with a sample size of 173 students. The technique used in sampling is cluster sampling. Data were collected using the McGill Friendship Questionnaire - Friendship Function scale. The analysis carried out was simple linear regression analysis. The results of the research show that quality of friendship has a positive influence on student hardiness at Islamic boarding schools in Padang City, with an influence contribution of 12.1%.